Research Progress on the Interaction Between SIRT1 and Mitochondrial Biochemistry in the Aging of the Reproductive System - Yang Li; Kai Kang; Huimingda Bao; Siqi Liu; Bangyi Zhao; Guangdong Hu; Jiang Wu (Biology)
The protein associated with the silencing information regulator 2-associated enzyme1 (SIRT1) is a highly conserved nicotinamide adenine dinucleotide (NAD+)-dependent deacetylase and a key member of the sirtuin family. SIRT1 plays an essential role in various cellular physiological processes, primarily localized in the nucleus but also active in the cytoplasm and mitochondria. Recent studies have demonstrated its capacity to delay aging in multiple organs and tissues, although its underlying mechanisms remain incompletely understood. Additionally, SIRT1 exerts a significant influence on metabolic regulation and genetic processes. As the primary source of cellular energy, mitochondria are central to numerous biological functions. Mitochondrial dysfunction has been implicated in the onset and progression of various diseases and is increasingly recognized for its role in aging-related processes. This article investigates the interaction between SIRT1 and mitochondria in regulating reproductive system aging and elucidates their potential mechanisms of action, providing insights for clinical research into reproductive system aging.